Patients’ experiences of deep brain stimulation for Parkinson's disease: a qualitative systematic review and synthesis - Mathers, J; Rick, C; Jenkinson, C; Garside, R; Pall, H; Mitchell, R; Bayliss, S; Jones, L (BMJ Publishing Group, 2016)
Objective - To review and synthesise qualitative research studies that have explored patients’ experience of deep brain stimulation (DBS) in advanced Parkinson's disease (PD). Design - Systematic review and meta-synthesis of 7 original papers, using metaethnography. Setting - Studies conducted in Denmark, France and Sweden. Participants - 116 patients who had undergone DBS and 9 spouses of patients. Results - Prior to surgery, the experience of advancing PD is one of considerable loss and a feeling of loss of control. There are significant hopes for what DBS can bring. Following surgery, a sense of euphoria is described by many, although this does not persist and there is a need for significant transitions following this. We suggest that normality as a concept is core to the experience of DBS and that a sense of control may be a key condition for normality. Experience of DBS for patients and spouses, and of the transitions that they must undertake, is influenced by their hopes of what surgery will enable them to achieve, or regain (ie, a new normality). Conclusions - There is a need for further qualitative research to understand the nature of these transitions to inform how best patients and their spouses can be supported by healthcare professionals before, during and after DBS. In assessing the outcomes of DBS and other treatments in advanced PD, we should consider how to capture holistic concepts such as normality and control. Studies that examine the outcomes of DBS require longer term follow-up.